Analisis Pendapatan Dan R/C Ratio Kentang Granola (Solanum tuberosum L.) di Kecamatan Paguyangan Kabupaten Brebes - Siti Mudmainah; Khusnul Khatimah (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Brebes Regency has a potato-producing center, precisely in Paguyangan Sub-District. The potato variety is a type of granola. Potato is a price that tends to fluctuate, and the cost of production is relatively high, causing the interest of farmers in growing potatoes to decline. The research aimed to determine the income received by potato farmers in the Paguyangan District. The analytical method used is the farm income formula to determine fixed costs, variable costs, revenues, and income. This research was held from June to August 2021. The results showed that the total cost (TC) was IDR86.858.345/ha/MT with details of a fixed price of IDR10.302.875/ha/MT and a variable cost of IDR78.560.1470/ha/MT. The revenue value (TR) of potato farming is IDR225,030,000/ha/MT. Based on the calculation, the income value of potato farming in Paguyangan District is IDR106.016,155/ha/MT.